Burden of laryngeal cancer attributable to occupational asbestos exposure in China: A comprehensive analysis from 1990 to 2021 - Bijuan Chen; Zhouwei Zhan; Sisi Yu; Jiali Huang; Chuying Chen; Jie Wang; Jianji Pan; Shaojun Lin; Yun Xu (PLoS ONE, 2025)
Background Laryngeal cancer attributable to occupational asbestos exposure remains a significant public health concern, particularly in industrialized regions. This study analyzes the burden, trends, and contributing factors of laryngeal cancer due to asbestos exposure in China from 1990 to 2021. Methods Data were obtained from the Global Burden of Disease Study (1990–2021). We analyzed age-standardized death rates, disability-adjusted life years (DALYs), years lived with disability (YLDs), and years of life lost (YLLs). Temporal trends were assessed using joinpoint and decomposition analyses, and an age-period-cohort (APC) model was applied to examine mortality and DALY trends across different cohorts. Results In 2021, there were 234 deaths and 4,430 DALYs due to laryngeal cancer attributable to occupational asbestos exposure, predominantly affecting males. Mortality rates declined from 1990 to 2008, followed by a rise until 2012, and a subsequent decline. YLDs showed a consistent increase over time. APC analysis revealed higher mortality and DALY rates in older age groups and earlier birth cohorts. Decomposition analysis indicated that epidemiological changes were the largest driver of increased deaths in men, followed by population growth and aging. For DALYs, aging and population growth were key drivers, while epidemiological changes mitigated the burden. Conclusions The burden of laryngeal cancer attributable to asbestos exposure has declined overall, but disability rates continue to rise, particularly among males. Effective strategies targeting prevention, early detection, and management of asbestos exposure are needed to reduce the disease burden in China.